The Development of Arabic Learning Evaluation based on Kahoot Application in Covid Outbreak l Tatwir Taqwim Ta'lim al-Lughah al-'Arabiyyah 'ala Asas Tatbiq Kahoot Khilala Jaikhah Covid - Yani, Meli Yani; Koderi, Koderi; Zulhanan, Zulhanan; Tubagus, Munir; Fauzan, Muhammad Sholeh (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2021)
This research based on the problems about learning evaluation in which was less attractive because it had not used evaluation instruments based on technology, especially the learning process during the Covid 19 outbreak. The purpose of this study was to develop an evaluation of Arabic learning for SMK in the form of an objective test based on Kahoot application during the Covid-19 outbreak. This research data were obtained from the interviews and students' responses to the evaluation. The interviews were conducted with groups of students as participants in the study, meanwhile, students' responses were confirmed to 32 students. The findings of this study indicated that the Arabic language objective test evaluation instrument by using the kahoot application was very feasible.  94% according to design experts, 96% according to material experts, 96% according to media experts. The results of the product effectiveness trial of the objective test evaluation instrument based on the kahoot application were 86% for one to one learner, 90% for the small group test, 88% for the field trial test. The development of an Arabic evaluation in the form of an objective test based on the Kahoot application during the Covid-19 outbreak had a significant effect on the evaluation of Arabic and could make students more active, independent and feel comfortable in the evaluation process. In line with that, this paper suggested the need for teacher and institutional involvement in solving the problem of community limitations in online learning evaluation.